Effectiveness of intermittent urinary catheterization in patients with neurogenic bladder: a systematic review protocol. (December 2016) - Fumincelli, Laís; Mazzo, Alessandra; Martins, José Carlos Amado; Henriques, Fernando Manuel Dias; Cardoso, Daniela; Rodrigues, Manuel Alves
Abstract : Review question/objective: The objective of this review is to investigate the effectiveness of the use of intermittent urinary catheterization in improving the quality of life (QoL) of patients with neurogenic bladder.